2021
DOI: 10.3389/fphar.2021.764351
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR, Molecular Docking, and MD Simulations of Anthraquinone Derivatives as PGAM1 Inhibitors

Abstract: PGAM1 is overexpressed in a wide range of cancers, thereby promoting cancer cell proliferation and tumor growth, so it is gradually becoming an attractive target. Recently, a series of inhibitors with various structures targeting PGAM1 have been reported, particularly anthraquinone derivatives. In present study, the structure–activity relationships and binding mode of a series of anthraquinone derivatives were probed using three-dimensional quantitative structure–activity relationships (3D-QSAR), molecular doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…ΔG total value is usually used to estimate the stability of protein-ligand complex. The lower values of ΔG total indicates that the complex is more stable ( Wang et al, 2021 ) and vice versa. It was computed as a sum of protein-ligand complex and the difference of PGAM1 protein and its ligands free energies.…”
Section: Resultsmentioning
confidence: 99%
“…ΔG total value is usually used to estimate the stability of protein-ligand complex. The lower values of ΔG total indicates that the complex is more stable ( Wang et al, 2021 ) and vice versa. It was computed as a sum of protein-ligand complex and the difference of PGAM1 protein and its ligands free energies.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have explored the effectiveness of compounds such as PGAM1 inhibitors (PGMI). 24 Based on the lead compound PGMI-004A, Wang et al 25 Furthermore, to screen novel inhibitors for PGAM1, Fang et al 28 explored the structure-activity relationships of anthraquinone compounds using 3D-QSAR and molecular dynamics simulation models and obtained satisfactory results that provide clues for the rational design of new inhibitors. Recently, Kanwal et al used in silico tools to evaluate phytochemical compounds that showed higher binding affinities than PGMI-004A.…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise correlation was used to select descriptors with values larger than 0.85. The correlation matrix constructed using all of the filtered descriptors was used to choose those having a greater association with activity for this investigation . The study comprised 11 variables having a cutoff correlation value of higher than 0.10 from the descriptor screening.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation matrix constructed using all of the filtered descriptors was used to choose those having a greater association with activity for this investigation. 55 The study comprised 11 variables having a cutoff correlation value of higher than 0.10 from the descriptor screening. (The correlation matrix, as well as the compound Pk i values of selected descriptors and intercorrelation between selected descriptors, are shown in Table 2.)…”
Section: Methodsmentioning
confidence: 99%